The NAIRU and informality in the Mexican labor market - Ana María Aguilar-Argaez; Carlo Alcaraz; Claudia Ramírez; Cid Alonso Rodríguez-Pérez (Banco de México, 2020)
The non-accelerating inflation rate of unemployment (NAIRU) is not directly observable and the presence of informal workers imposes an additional challenge in its estimation. Countries with large informal sectors, traditional measures might not depict labor slack properly, as it has the wage flexibility needed to incorporate formal workers that cannot find a formal job. In this paper, we present an estimation of the traditional NAIRU for Mexico and an alternative measure that includes informality as an indicator of labor underutilization. We find that both measures of NAIRU and the associated labor market slack indicators follow similar patterns over time. However, the slack estimated with the indicator that includes informality seems to predict inflationary pressures more accurately when the unemployment gap is close to zero.
Keywords: E26; E32; E52; 330; Unemployment; Informality; NAIRU; Business cycle